2022
DOI: 10.1093/rheumatology/keac063
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings of calcium pyrophosphate deposition disease at metacarpophalangeal joints

Abstract: Objective To explore the spectrum of articular and peri-articular ultrasound (US) findings at metacarpophalangeal (MCP) joints in calcium pyrophosphate (CPP) deposition disease (CPPD). Methods Consecutive CPPD patients (chronic CPP crystal inflammatory arthritis or osteoarthritis (OA) with CPPD), and age- and sex-matched controls with rheumatoid arthritis (RA) were prospectively enrolled. Patients underwent bilateral US exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…2 Even though the difference in the degree of the erosiveness is not well defined in the literature, nevertheless the item 'erosiveness' cannot be fully discriminative, though much more relevant in RA. 6 However, the erosions at the craniocervical region (atloepistrophic joint) are quite distinctive; we showed they may occur already in early RA 7 and have very rarely been described in CPPD. Therefore, one possibility to discriminate between an acute attack of RA or an acute arthritis episode CPPD-related, may be the demonstration of CC at the craniocervical region, in the presence of an acute flare of pain.…”
Section: Introductionmentioning
confidence: 61%
“…2 Even though the difference in the degree of the erosiveness is not well defined in the literature, nevertheless the item 'erosiveness' cannot be fully discriminative, though much more relevant in RA. 6 However, the erosions at the craniocervical region (atloepistrophic joint) are quite distinctive; we showed they may occur already in early RA 7 and have very rarely been described in CPPD. Therefore, one possibility to discriminate between an acute attack of RA or an acute arthritis episode CPPD-related, may be the demonstration of CC at the craniocervical region, in the presence of an acute flare of pain.…”
Section: Introductionmentioning
confidence: 61%
“…Beyond CPP deposits, radiographic features associated with CPPD include osteoarthritis distribution in specific joints, distinct from the typical osteoarthritis involvement [12 ▪ ]. These include particularly second and third metacarpophalangeal joints, characterized by prominent ‘hook-like’ osteophytes and the wrist, with joint space narrowing or osteophyte at the scapho-trapezium joint, and scapho-lunate advanced collapse (SLAC) [37]. These features aid in distinguishing CPPD from other conditions even if they do not appear to be universally present in all patients with CPPD.…”
Section: Describing Calcium Pyrophosphate Deposition Through Imagingmentioning
confidence: 99%
“…Nevertheless, some studies have questioned the specificity of the DC sign for gout as it has been reported in calcium pyrophosphate deposition (CPPD), [4][5][6] with a prevalence ranging from 7.1% 6 to 20.2%. 5 A previous case report has demonstrated that the deposition of CPP crystals in capsules and/or ligaments appearing to be located on top of the hyaline cartilage generates a pseudo DC sign in CPPD disease.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%